Pencegahan Korupsi Dana Desa Dalam Rangka Mewujudkan Desa Antikorupsi - Judy Marria Saimima; Juanrico A.S. Titahelu; Patrick Corputty; Muammar (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2023)
Abstract This paper aims to describe and analyze how the form of corruption prevention of village funds can ideally be carried out to realize an anti-corruption village. This paper uses a normative type of research. The approach used in this paper is a conceptual approach (conceptual approach) and an analytical approach (analytical approach). The discussion in the paper presents that so far the eradication of corruption has focused more on the downstream region by relying on criminal legal means. the eradication of corruption should ideally be pursued optimally in the most upstream areas, namely prevention areas. This includes efforts to prevent corruption of village funds, which have often become